2016
DOI: 10.1002/jcb.25469
|View full text |Cite
|
Sign up to set email alerts
|

Titanium With Nanotopography Induces Osteoblast Differentiation by Regulating Endogenous Bone Morphogenetic Protein Expression and Signaling Pathway

Abstract: We aimed at evaluating the effect of titanium (Ti) with nanotopography (Nano) on the endogenous expression of BMP-2 and BMP-4 and the relevance of this process to the nanotopography-induced osteoblast differentiation. MC3T3-E1 cells were grown on Nano and machined (Machined) Ti surfaces and the endogenous BMP-2/4 expression and the effect of BMP receptor BMPR1A silencing in both osteoblast differentiation and expression of genes related to TGF-β/BMP signaling were evaluated. Nano supported higher BMP-2 gene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 42 publications
5
50
0
9
Order By: Relevance
“…These results lend support to our initial hypothesis that collagen coating of nanotopographic Ti surface enhances in vitro osteogenesis, which could be due to increasing and/or accelerating osteoblast differentiation as showed for already differentiated osteoblasts as well as inducing osteoblast differentiation under nonosteogenic conditions . Considering that nanotopography increases the endogenous production of BMP‐2 and that collagen interacts with integrin receptors to regulate osteoblast differentiation induced by BMP‐2, it is possible to suggest that the synergic positive effect of nanotopography and collagen coating on in vitro osteogenesis observed here is, at least in part, modulated by BMP‐2 signaling pathway …”
Section: Discussionsupporting
confidence: 88%
“…These results lend support to our initial hypothesis that collagen coating of nanotopographic Ti surface enhances in vitro osteogenesis, which could be due to increasing and/or accelerating osteoblast differentiation as showed for already differentiated osteoblasts as well as inducing osteoblast differentiation under nonosteogenic conditions . Considering that nanotopography increases the endogenous production of BMP‐2 and that collagen interacts with integrin receptors to regulate osteoblast differentiation induced by BMP‐2, it is possible to suggest that the synergic positive effect of nanotopography and collagen coating on in vitro osteogenesis observed here is, at least in part, modulated by BMP‐2 signaling pathway …”
Section: Discussionsupporting
confidence: 88%
“…The osseoinductive capacity makes this nanotopography an appealing model of investigation of the signaling pathways triggered by an osteogenic microenvironment that drive the process of osseointegration . In this context, we have already shown that this surface regulates several cell machinery components, including integrins, in order to induce osteoblast differentiation …”
Section: Discussionmentioning
confidence: 99%
“…In the studies [34,35] the nanotopography-induced osteogenic differentiation of the MC3T3-E1 cells is addressed. The corresponding analysis of the samples was performed at day 7 and day 4, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The papers of Karazisis et al [37] and Freitas et al [38] present the effect of Ti nanotopography on bone response by using the same method as Castro-Raucci et al [34] and Kato et al, [35] however applying an in vivo approach. The publication history of the articles [34,35] indicates that the studies are performed in a logical order: from in vitro to in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation